1998
DOI: 10.1677/joe.0.159r009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting on insulin receptor-related receptor messenger ribonucleic acid in rat kidney

Abstract: The insulin receptor-related receptor (IRR), a member of the insulin receptor tyrosine kinase family, has structural homology to the insulin receptor (IR) and the IGF-I receptor (IGF-IR). The ligand, gene regulation and biological function of the IRR are not known. Because mRNAs for both the IR and IGF-IR are increased by nutrient restriction, we used RNase protection assays to assess the effects of fasting 48 h on IRR mRNA in kidneys of rats. We compared the changes in IRR with those in IR and IGF-IR mRNAs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The PCR protocol for PPARg consisted of 2 min of denaturing at 95C, followed by 30 cycles with 95C denaturing for 0 s, 55C annealing for 5 s and 72C extension for 35 s. b-Actin was used as a control to account for any variations due to efficiencies of the reverse transcription and PCR. In the present study, b-actin was not found to be significantly different across treatment, results which are in line with previous studies showing that it remains stable under fasting conditions [8,25]. The PCR protocol for b-actin consisted of 2 min of denaturing at 95C, followed by 30 cycles with 95C denaturing for 0 s, 60C annealing for 5 s and 72C extension for 12 s. Detection of the fluorescent product was carried out at the end of the 72C extension period.…”
Section: Real-time Quantitative Pcrsupporting
confidence: 93%
“…The PCR protocol for PPARg consisted of 2 min of denaturing at 95C, followed by 30 cycles with 95C denaturing for 0 s, 55C annealing for 5 s and 72C extension for 35 s. b-Actin was used as a control to account for any variations due to efficiencies of the reverse transcription and PCR. In the present study, b-actin was not found to be significantly different across treatment, results which are in line with previous studies showing that it remains stable under fasting conditions [8,25]. The PCR protocol for b-actin consisted of 2 min of denaturing at 95C, followed by 30 cycles with 95C denaturing for 0 s, 60C annealing for 5 s and 72C extension for 12 s. Detection of the fluorescent product was carried out at the end of the 72C extension period.…”
Section: Real-time Quantitative Pcrsupporting
confidence: 93%
“…Riboprobes were prepared by in vitro transcription and purified on 5% acrylamide/8 m urea gel. RPA were carried out as previously described (Chrysis et al ., 1998). Briefly, 20 µg total brain RNA was hybridized overnight at 45 °C with biotin‐labeled riboprobes (nestin and cyclophilin).…”
Section: Methodsmentioning
confidence: 99%
“…RPA was performed as reported previously (Chrysis et al, 1998). Briefly, 20 g samples of CB total RNA were hybridized overnight at 45°C with biotin-labeled riboprobes (3 fmol of cyclophilin, 2.5 fmol of Bcl-x and Bax, or 3 fmol of cyclophilin, 3 fmol of Bad, and 2 fmol of Bcl-2).…”
Section: Methodsmentioning
confidence: 99%